2(h-1)=3(h+1)

Simple and best practice solution for 2(h-1)=3(h+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(h-1)=3(h+1) equation:


Simplifying
2(h + -1) = 3(h + 1)

Reorder the terms:
2(-1 + h) = 3(h + 1)
(-1 * 2 + h * 2) = 3(h + 1)
(-2 + 2h) = 3(h + 1)

Reorder the terms:
-2 + 2h = 3(1 + h)
-2 + 2h = (1 * 3 + h * 3)
-2 + 2h = (3 + 3h)

Solving
-2 + 2h = 3 + 3h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-3h' to each side of the equation.
-2 + 2h + -3h = 3 + 3h + -3h

Combine like terms: 2h + -3h = -1h
-2 + -1h = 3 + 3h + -3h

Combine like terms: 3h + -3h = 0
-2 + -1h = 3 + 0
-2 + -1h = 3

Add '2' to each side of the equation.
-2 + 2 + -1h = 3 + 2

Combine like terms: -2 + 2 = 0
0 + -1h = 3 + 2
-1h = 3 + 2

Combine like terms: 3 + 2 = 5
-1h = 5

Divide each side by '-1'.
h = -5

Simplifying
h = -5

See similar equations:

| (2x-7/12)+x=(2x+7/2)+3 | | 5x^2+7x+95=0 | | .3333(5x-8)=3 | | y=2x+22/5 | | onethird(5x-8)=3 | | 5y=2x+22 | | -4x+13-2x=3x-11 | | 2x-5/3+5=8 | | -9m+m^2=0 | | (11b+9)(2b-3)=0 | | 2(x-7)-1=5(3x+1) | | 3x/5+2x=0 | | (t/8+5)=7 | | x=3x+7(x-8) | | -8=4(9-2)+4 | | 3x-x/8=30 | | 7-3r=r-4(5-2/5r) | | 6=4/5+5 | | -13=h-1 | | 0-4x+7=11 | | g(t)=3t-3 | | 2.8=6/4 | | f(x+8)=(x+8)2-3(x+8)-2 | | 0.3x^5+0.4x^4-8x^3-7x^2+23x+22=0 | | 3g-4=7g+12 | | 15=3n/5 | | -3/4+3=-12 | | 2p=5y | | b^2-b-9=0 | | 3/b-3-b/b-3 | | x/81=80/22 | | 3-b/b-3 |

Equations solver categories